Evaluación de la gestión y calidad de servicio que brinda el Registro de la Propiedad del Cantón Bolívar. - Bravo Vera, Génesis Belén (2018)
The Property Registry of the Bolívar canton is an institution attached to the Autonomous Municipal Government of said jurisdiction, which must comply with all the laws in the different areas that for its effect were created, in this institution there are faults in its organizational composition because In the process of providing services delay is generated, in addition, although the institution has several strengths and opportunities that can be used in favor of the institution, there are also several weaknesses and threats that can mean danger in the future. The bibliographical research allowed to define the variables of study, and from that to formulate the field research that was based on the use of instruments for the collection of information such as the survey directed to the clients to diagnose the service and the interview made to the director. of the institution to know the processes and functions that occur in the institution, in addition to the methods that were essential for the processing and incorporation of classified information to the improvement proposal. In the field investigation it was possible to verify that the Property Registry of the Bolívar canton is structured under an organization by process, but that its distribution does not comply with the objective of optimizing resources, especially time. That is why the need arises to structure a proposal that includes the areas where the shortcomings are found, the planning of improvement actions as well as their respective follow-up.